"Process of strategic planning and cognitive diversity as determinants of cohesiveness and performance". Issue 1 (6th July 2020) - Nowak, Radoslaw
Abstract : Purpose: The purpose of this paper is to investigate the effects of the process of strategic planning on cohesiveness and performance in cognitively diverse units. Design/methodology/approach: This study uses structural equation modeling (SEM) to analyze an original dataset collected from employees working in healthcare organizations in the United Sates. Findings: This study finds the negative effects of cognitive differences among employees on a unit's cohesiveness and performance and the positive moderating effects of the process of strategic planning on such relationships. Consequently, revealing the cohesiveness enhancing function of the process of strategic planning. Originality/value: The study contributes to past research by revealing that business organizations could use the process of strategic planning to enhance their internal cohesiveness, in turn improving their business performance. This study explains that when the process of planning clearly defines an organization's mission, goals and implementation plans, employees working in highly diverse units will be more likely to better understand, accept and in turn also support their organization as a whole and its critical strategic goals. This should increase internal cohesiveness and lead leading to better performance.